Advances and limitations of the Environmental Seismic Intensity scale (ESI 2007) regarding near-field and far-field effects from recent earthquakes in Greece: implications for the seismic hazard assessment - Papanikolaou, I. D.; Papanikolaou, D. I.; Lekkas, E. L. (Geological Society, London, Special Publications, 2009)
The new Environmental Seismic Intensity scale (ESI 2007), introduced by INQUA, incorporates the advances and achievements of palaeoseismology and earthquake geology and evaluates earthquake size and epicentre solely from the earthquake environmental effects (EEE). This scale is tested and compared with traditional existing scales for the 1981 Alkyonides earthquake sequence in the Corinth Gulf (Ms=6.7, Ms=6.4, Ms=6.3), the 1993 Pyrgos event (Ms=5.5) and the 2006 Kythira event (Mw=6.7). These earthquakes were of different magnitudes, focal mechanisms and focal depths and produced well-documented environmental effects. The ESI 2007 intensity values and the isoseismal pattern for the 1993 Pyrgos and the 2006 Kythira events are similar to those resulting from the traditional scales, demonstrating that for moderate intensity levels (VII and VIII) the ESI 2007 and the traditional scales comply well. In contrast, the 1981 Alkyonides earthquake sequence shows that there is an inconsistency between the ESI 2007 and the traditional scales both in the epicentral area, where higher ESI 2007 intensity values have been assigned, and for the far-field effects. The ESI 2007 scale offers higher objectivity in the process of assessing macroseismic intensities, particularly in the epicentral area, than traditional intensity scales that are influenced by human parameters. The ESI 2007 scale follows the same criteria-environmental effects for all events and can compare not only events from different settings, but also contemporary and future earthquakes with historical events. A reappraisal of historical earthquakes so as to constrain the ESI 2007 scale may prove beneficial for seismic hazard assessment by reducing the uncertainty implied in the attenuation laws, which constitute one of the most important seismic hazard parameters.